Evolutionary engineering of a glycerol‐3‐phosphate dehydrogenase‐negative, acetate‐reducing Saccharomyces cerevisiae strain enables anaerobic growth at high glucose concentrations. Issue 1 (4th September 2013) - Guadalupe‐Medina, Víctor; Metz, Benjamin; Oud, Bart; van, Charlotte M.; Mans, Robert; Pronk, Jack T.; van, Antonius J. A.
Summary Glycerol production by Saccharomyces cerevisiae, which is required for redox‐cofactor balancing in anaerobic cultures, causes yield reduction in industrial bioethanol production. Recently, glycerol formation in anaerobic S. cerevisiae cultures was eliminated by expressing Escherichia coli (acetylating) acetaldehyde dehydrogenase (encoded by mhpF) and simultaneously deleting the GPD1 and GPD2 genes encoding glycerol‐3‐phosphate dehydrogenase, thus coupling NADH reoxidation to reduction of acetate to ethanol. Gpd– strains are, however, sensitive to high sugar concentrations, which complicates industrial implementation of this metabolic engineering concept. In this study, laboratory evolution was used to improve osmotolerance of a Gpd–mhpF‐expressing S. cerevisiae strain. Serial batch cultivation at increasing osmotic pressure enabled isolation of an evolved strain that grew anaerobically at 1 M glucose, at a specific growth rate of 0.12 h−1. The evolved strain produced glycerol at low concentrations (0.64 ± 0.33 g l−1). However, these glycerol concentrations were below 10% of those observed with a Gpd+ reference strain. Consequently, the ethanol yield on sugar increased from 79% of the theoretical maximum in the reference strain to 92% for the evolved strains. Genetic analysis indicated that osmotolerance under aerobic conditions required a single dominant chromosomal mutation, and one further mutation in the plasmid‐borne mhpF gene for anaerobic growth.